Factors causing insomnia in postmenopausal women - Karpeta-Pawlak, Iwona Ewa; Wolińska, Weronika; Mroczek, Bożena (Family Medicine & Primary Care Review, 2017)
Background . Insomnia is the most common sleep disorder among adult people. It causes tiredness, difficulties in focusing, loss of energy, increased sensitivity, and irritability. Insomnia may develop into a chronic sleep disorder which has a direct negative impact on the quality of life of the affected person and it limits their capabilities of functioning in society. Objectives . The study objective was to seek relationships between age, the use of HRT , occurrence of depression symptoms and chronic conditions and insomnia in postmenopausal women. Material and methods . The study was conducted on 128 women, students of the University of the Third Age in Stargard. The median age was 65 years and ranged from 47 to 82 years old. The study was conducted with the use of the Insomnia Severity Index, the Beck Depression Inventory and the authors’ own questionnaire. Results . Various degrees of insomnia were diagnosed in 69 women (53.91%). A statistically significant relationship was found between insomnia and age (x2 = 27.48; p = 0.007), occurrence of depression (x2 = 12.93; p = 0.005), and depression symptoms (x2 = 81.86; p < 0.001). The study revealed no statistically significant relationship between insomnia and the use of HRT , or the existence of chronic conditions. Conclusions . Age and depression symptoms have a significant impact on the occurrence of insomnia. However, the use of HRT or preexisting chronic conditions have no key influence on the occurrence of insomnia.